Study of Nutritive value and Preliminary Phytochemical Screening of the leaf extract of Ficus nervosa Heyne ex Roth, a lesser known medicinal plant - R.N.S. Yadav, Rajesh Kumar Shah, (Journal of Phytology, 2015)
The present study was undertaken to evaluate the nutritive value and phytochemical constituents in the leaf extract of Ficus nervosa Heyne ex Roth which is traditionally used as medicinal plant. A preliminary phytochemical analysis was carried out and concluded the presence of various phytochemicals. Biochemical estimation of total carbohydrate, protein, free amino acid, lipid, ascorbic acid, vitamin E, crude fibre, alkaloids, flavonoids and phenols were performed by standard procedures. The nutritive value (K cal/100 gm) was found to be 90.6 K cal/100g. Phytochemical studies indicated that the leaf contain a broad spectrum of secondary metabolites and presence of these medicinally important bioactive compounds justifies their use in the traditional medicines for the treatment of different diseases